Antibacterial and antibiofilm properties of ZnO nanoparticles synthesis using gum arabic as a potential new generation antibacterial agent - Norlin, Pauzi; Norashikin, Mat Zain; Rajaletchumy, Veloo Kutty; Hafizah, Ramli (Elsevier, 2020)
This study aimed to investigate the antibacterial properties of gum arabic-ZnO nanoparticles. The antibacterial and antibiofilm activities of gum arabic-ZnO nanoparticles were evaluated against Staphylococcus aureus and Escherichia coli. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) value of gum arabic-ZnO nanoparticles for S. aureus and E. coli was 31.25 lg/mL, 62.5 lg/mL and 62.5 lg /mL, 125 mg/mL respectively. At higher concentrations above 500 lg/mL, the percentage of toxicity to biofilm was observed more than 50% for both S. aureus and E. coli. Therefore gum arabic-ZnO nanoparticles are suggested as a natural new generation antibacterial agent.